2019
DOI: 10.3389/fnhum.2019.00356
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nervous System Activity in Preschoolers Who Stutter

Abstract: BackgroundIn our Dynamic Pathways, account, we hypothesized that childhood stuttering reflects an impairment in speech sensorimotor control that is conditioned by cognitive, linguistic, and emotional factors. The purpose of this study was to investigate potential differences in levels of sympathetic arousal during performance of speech and non-speech tasks between children who do and do not stutter.MethodsSeventy-two preschool-aged children participated in the study, 47 children who stutter (CWS; 38 boys) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 71 publications
0
11
1
Order By: Relevance
“…Compared to CWNS, several studies have found temperamental differences in some CWS, such as increased anger or frustration, and greater difficulty regulating emotions or adapting to change (Anderson, Pellowski, Conture, & Kelly, 2003;Eggers, De Nil, & Van den Bergh, 2010;Karrass et al, 2006). However, others' and our research have not revealed temperamental differences between young CWS and CWNS using parent report measures (Kefalianos, Onslow, Ukoumunne, Block, & Reilly, 2014, 2017Walsh, Smith, Christ & Weber, 2019).…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…Compared to CWNS, several studies have found temperamental differences in some CWS, such as increased anger or frustration, and greater difficulty regulating emotions or adapting to change (Anderson, Pellowski, Conture, & Kelly, 2003;Eggers, De Nil, & Van den Bergh, 2010;Karrass et al, 2006). However, others' and our research have not revealed temperamental differences between young CWS and CWNS using parent report measures (Kefalianos, Onslow, Ukoumunne, Block, & Reilly, 2014, 2017Walsh, Smith, Christ & Weber, 2019).…”
contrasting
confidence: 64%
“…Data from 22 preschool CWS (19 boys and three girls; M = 53.3 months, SD = 6.15, range: 46-71) were included in this study. These children participated in a larger investigation conducted by the Purdue Stuttering Project comparing behavioral indices of temperament and SNS responses during speech and oral motor tasks in preschool CWS and their fluent peers (Walsh et al, 2019). We included children from the larger study in the current study if they produced at least six stuttered and six fluent utterances during a picture description task, described below.…”
Section: Participantsmentioning
confidence: 99%
“…While social anxiety is commonly reported in adults who stutter, the same has not been consistently reported in children who stutter. Direct examination of emotional processing in children who stutter has been rare, though some studies have reported subtle differences in CWS in terms of autonomic nervous system responses to challenging speech tasks (nonword repetition; (Tumanova & Backes, 2019)) or emotionally stressful stimuli ((Jones et al, 2014; Walsh et al, 2019). The current BBS results suggest that brain networks linked to emotional regulation and their connectivity with cognitive control networks may differentiate children who stutter.…”
Section: Discussionmentioning
confidence: 99%
“…Psychophysiological research with children who stutter is somewhat limited. However, recently a number of studies have examined CWS's autonomic nervous system response to such speaking conditions as picture naming, picture description, and non-word repetition (Jones et al, 2014 , 2017 ; Zengin-Bolatkale et al, 2015 , 2018 ; Choi et al, 2016 ; Tumanova and Backes, 2019 ; Walsh and Usler, 2019 ; Walsh et al, 2019 ). Results of these studies generally indicate that CWS do not have an elevated level of autonomic arousal during speaking.…”
Section: Electrodermal Activity As a Measure Of Emotional Reactivitymentioning
confidence: 99%
“…Results of these studies generally indicate that CWS do not have an elevated level of autonomic arousal during speaking. However, between-group differences in arousal, based on age (Zengin-Bolatkale et al, 2015 ) and task complexity (Tumanova and Backes, 2019 ), as well as within-CWS differences, based on stuttering chronicity (Zengin-Bolatkale et al, 2018 ), and speech fluency (Walsh et al, 2019 ) have been observed.…”
Section: Electrodermal Activity As a Measure Of Emotional Reactivitymentioning
confidence: 99%